Je tek primeren za sklepni hrustanec? - Veselko, Matjaž (Šport (Ljubljana), 2013)
Healthy cartilage allows for normal function of loaded synovial joints and thus sports activity. Long-term cyclic loading, especially impact loading of the cartilage can cause structural changes that influence balance of the catabolic-anabolic processes in chondral matrix. Deterioration of chondral matrix in excessive loading can become irreversible. On the other hand, loading and motion are beneficial for maintaining normal structure and composition of chondral matrix. Chondroprotectives such as glucosamine, chondroitin sulfate, and other nutritients, such as antioxidantes have beneficial effect on maintaining cartilage. It appears that long-distance running does not increase the risk of osteoarthritis in healthy individuals and may even have some protective effect against joint degeneration.
Keywords: arthritis; artroza; cartilage; hrustanec; regeneracija; regeneration; running sports; sklepni hrustanec; sport; šport; tek